Electrochemical Kinetics of Ag/Ag+ and TMPD|TMPD+. in the Room-Temperature Ionic Liquid [C4mpyrr][NTf2]; toward Optimizing Reference Electrodes for Voltammetry in RTILs - Rogers, E; Silvester, D; Jones, S; Aldous, L; Hardacre, C; Russell, A; Davies, S; Compton, R (ACS Publications, 2007)
The voltammetry and kinetics of the Ag|Ag+ system (commonly used as a reference electrode material in both protic/aprotic and RTIL solvents) was studied in the room-temperature ionic liquid N-buty1-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, [C4mpyrr] [NTf2] on a 10 μm diameter Pt electrode. For the three silver salts investigated (AgOTf, AgNTf2, and AgNO3, where OTf- = trifluoromethanesulfonate, NTf2- = bis(trifluoromethylsulfonyl)imide, and NO 3- = nitrate), the voltammetry gave rise to a redox couple characteristic of a "deposition/stripping" process at the platinum electrode surface. Using potential step chronoamperometry, the diffusion coefficients of AgOTf, AgNTf2, and AgNO3 were found to be 1.05, 1.17, and 5.00 × 10-11 m2 s-1. All three voltammograms were theoretically modeled to reveal surprisingly slow standard electrochemical rate constants, k0, of 2.0, 1.5, and 0.19 × 10-4 cm s-1 respectively for the Ag +|Ag0 couple. As a potentially faster alternative to the Ag|Ag+ system, the voltammetry and kinetics of the TMPD|TMPD + system (where TMPD = N,N,N′,N′-tetramethyl-p- phenylenediamine) was also studied, using neutral TMPD and two TMPD radical cation salts, with BF4- and NTf2- counter anions. Diffusion coefficients for TMPD, TMPD+BF 4-, and TMPD+NTf2- were calculated to be 1.84, 1.35, and 1.43 × 10-11 m2 s-1 respectively, and a k0 value of 2.6-2.8 × 10-3 cm s-1 was obtained from theoretical fitting of the cyclic voltammetry. This number is an order of magnitude larger than that for the Ag|Ag+ system, allowing for the suggestion that the TMPD|TMPD+ system may be more suitable than the Ag|Ag+ system as a redox couple for use in reference electrodes for ionic liquids. © 2007 American Chemical Society.